IMPLEMENTATION OF TAFSIR MAQASIDI (A Study of Prohibition Verses About Syuhada As a Dead People) - Afdal, Rezki; Farhani, Aan; Mustafa, Mujtaba (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The interpretation of death’s theme in the Qur’an immediately stagnated when mufassir discuss it in eschatolical topic. It can be talked again in academic discourse by starting to look for the maqasid behind a verse by reading the context and the historical relations that surround it. Therefore, this study will apply tafsir maqasid as a theory to interpret the verses of death related with escatological theme, in this case QS. Al-Baqarah/2: 154 and QS. Ali ‘Imran/3: 169. Most mufassir commented on these verses according to explicit text whitout trying to identificate to other interpretation; that the Believers who fight for Allah will live in other world. Through this research, it is found other alternative interpretation; that these verses are not only explain about how syuhada live after die but also state indicate the importance of protecting religion even sacrificing one’s life. Besides that, it is also conluded that death is a part of God’s pleasure.